2017
DOI: 10.1002/admi.201700237
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and Irreversible Reactions of Trimethylaluminum with Common Organic Functional Groups as a Model for Molecular Layer Deposition and Vapor Phase Infiltration

Abstract: Organic–inorganic hybrid materials are of great demand not at least for their enormous application potential in flexible devices. Atomic or molecular layer deposition (ALD or MLD) and vapor phase infiltration (VPI) offer novel pathways for the fabrication of such hybrids, but a clear understanding of the chemistry between the vaporized precursors and functional molecules is still lacking. In this work, the interactions between trimethylaluminum (TMA) and the organic functional groups OH, NH2, and NO2 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 72 publications
6
47
0
Order By: Relevance
“…Additionally, EDS line scan shown in Figure S2 for a nanolaminate sample shows no or little Zn within the sub-surface growth. Subsurface diffusion of ALD precursors into polymers and other soft substrates is a relatively well known phenomenon [48,49,50,51,52]. For instance Sun et al reported very similar looking sub-surface growth deposited on polyamide-6, and discovered that thinner subsurface growth had higher fracture strain [51].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, EDS line scan shown in Figure S2 for a nanolaminate sample shows no or little Zn within the sub-surface growth. Subsurface diffusion of ALD precursors into polymers and other soft substrates is a relatively well known phenomenon [48,49,50,51,52]. For instance Sun et al reported very similar looking sub-surface growth deposited on polyamide-6, and discovered that thinner subsurface growth had higher fracture strain [51].…”
Section: Resultsmentioning
confidence: 99%
“…Previous work on another metalcone film, alucone, suggests that the observed conversion process in alucone is driven by the reaction of water or oxygen with the carbon or metal atoms in the film, splitting the CO or metal–oxygen bonds, respectively . This reaction with oxygen or water is exothermic or slightly endothermic at ambient conditions for alucone films and can produce a mixture of formaldehyde, glycols, and acid products .…”
Section: Resultsmentioning
confidence: 77%
“…Yang et al concluded in their study of phenyls, substituted with −OH, −NH 2 , or −NO 2 groups, that whenever −OH groups were present TMA would react irreversibly with it. 52 MH consists of three hydroxyl groups per repeating unit, or 22 per molecule (see Figure 1 ). It is therefore reasonable to assume that the main initial process for alumina infiltration of MH involves the reaction between TMA and these hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%